Philosophy can’t be learned! Plato as a true master and writing as “Protreptical Alusion” - Migliori, Maurizio (Revista Archai, 2011)
On this article, we deal with some fundamental aspects of the “Tübingen-Milan school” of interpretation of Plato’s though. We dedicate special attention to two of Plato’s key texts to the new hermeneutics: the conclusive part of the Phaedrus and the Seventh Letter. We’ll try to elucidate some of the base concepts that determine this alternative way of reading the philosopher, such as indirect tradition, unwritten doctrines and supreme principles’ theory.